The Impact Of Absorption, Ergonomics, And Physical Work Environment On Enhancing Women's Productivity In Industry - Ipmawan, Hasan; Kristanto, Dwi; Pakpahan, Maruji; Naryoto, Pambuko; Kuncoro, Aris Wahyu (Sean Institute, 2025)
This study examines the impact of absorption, ergonomics, and the physical work environment on enhancing women's productivity in the industrial sector. Absorption refers to an individual’s level of engagement and focus on tasks, which, while having a positive relationship with productivity, was found to be statistically insignificant in this study. Conversely, ergonomics demonstrated a significant positive effect, highlighting the importance of workplace designs that reduce fatigue and enhance efficiency. Furthermore, the physical work environment exhibited a strong and highly significant impact on productivity, underscoring the critical role of elements such as lighting, ventilation, and spatial arrangement in fostering employee performance. Data were collected from female employees at PT Surya Toto Indonesia Tbk using a purposive sampling technique and analyzed through SmartPLS version 4. The findings emphasize the need for organizations to address barriers to absorption, prioritize ergonomic workplace designs, and invest in conducive physical work environments to maximize productivity.